Learning with farmers and traders in Mozambique - Natha, Edson (Technical Centre for Agricultural and Rural Cooperation, 2019)
As part of an experience capitalization process, a simple questionnaire or a set of templates can help collect and organise information, and prepare a short document. But even more important is to ensure that the beneficiaries of a project actively join the process. These have been the two main elements of the new experience capitalization initiatives startin in Mozambique.